2023
DOI: 10.2174/0929867330666230126100638
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide (H2S): As a Potent Modulator and Therapeutic Prodrug in Cancer

Abstract: Hydrogen sulfide (H2S) is an endogenous gaseous molecule present in all living organisms and has been traditionally studied for its toxicity. Interestingly, increased understanding of H2S effects in organ physiology has recently shown its relevance as a signalling molecule, with potentially important implications in variety of clinical disorders, including cancer. H2S is primarily produced in mammalian cells under various enzymatic pathways. A developing focus of H2S is a blooming hotspot that studies chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 270 publications
0
2
0
Order By: Relevance
“…The evidence indicates that H 2 S plays a vital role in multiple pathological and physiological processes, such as anti-inflammation ( Mohammed et al, 2021 ), anti-apoptosis ( Fouad et al, 2020 ), anti-oxidative stress ( Tocmo and Parkin, 2019 ), blood pressure reduction ( Greaney et al, 2017 ; Zaorska et al, 2019 ), and the regulation of cell survival/death, cell proliferation/hypertrophy and cell differentiation ( Zhang et al, 2017 ). Hence, H 2 S participates in many diseases, such as lung diseases ( Pacitti et al, 2021 ), ischemia/reperfusion injury ( Krylatov et al, 2021 ), and cancers ( Shackelford et al, 2021b ; Khattak et al, 2022 ; Faris et al, 2023 ). In recent years, many studies have revealed that H 2 S has the dual effects of anticancer and cancer promotion in HCC, but the relevant mechanisms are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence indicates that H 2 S plays a vital role in multiple pathological and physiological processes, such as anti-inflammation ( Mohammed et al, 2021 ), anti-apoptosis ( Fouad et al, 2020 ), anti-oxidative stress ( Tocmo and Parkin, 2019 ), blood pressure reduction ( Greaney et al, 2017 ; Zaorska et al, 2019 ), and the regulation of cell survival/death, cell proliferation/hypertrophy and cell differentiation ( Zhang et al, 2017 ). Hence, H 2 S participates in many diseases, such as lung diseases ( Pacitti et al, 2021 ), ischemia/reperfusion injury ( Krylatov et al, 2021 ), and cancers ( Shackelford et al, 2021b ; Khattak et al, 2022 ; Faris et al, 2023 ). In recent years, many studies have revealed that H 2 S has the dual effects of anticancer and cancer promotion in HCC, but the relevant mechanisms are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen sulfide (hereafter referred to as H 2 S) the latest identified endogenous gaseous mediator, was once considered a foul-smelling and hazardous gas found in the environment [ 9 ]. Recently, H 2 S has gained increasing attention as an important player in modulating a wide range of physiological and pathological conditions [ 10 , 11 ]. In mammals, similar to NO and CO, three enzymes including cystathionine γ-lyase (CSE), cystathionine β-synthase (CBS) and the 3-mercaptopyruvate sulphur transferase (3-MPST) are responsible for H 2 S generation.…”
Section: Introductionmentioning
confidence: 99%